P 44 Brisk jerk reflexes in a CMT case – novel heterozygous variant c.785T>C; p.Leu262Pro in KIF5A explaining the mixed phenotype. Issue 10 (October 2017) - Dohrn, M.F.; Glöckle, N.; Mulahasanovic, L.; Sprecher, A.; Biskup, S.; Claeys, K.G.; Schulz, J.B.; Gess, B.
Abstract : Introduction: Charcot-Marie-Tooth (CMT) disease is a progressively disabling syndrome phenotypically comprising distal muscle weakness and atrophy, foot deformities, sensory loss, and reduced or absent tendon reflexes. In spastic paraplegia (SPG), a hereditary disorder affecting the upper motor neuron only, pareses are spastic, and deep tendon reflexes increased. Mixed forms between both diseases have been previously described (Liu et al., 2014 ). By multiple gene panel based analysis using next-generation-sequencing (NGS), we herein identified the novel variant c.785T>C; p.Leu262Pro in KIF5A as the putative cause of a mixed CMT and SPG phenotype. Methods: The patient's examination took place in the neuromuscular outpatient clinic of the RWTH Aachen University hospital. After obtaining the patient's informed consent, the molecular genetic analysis of an NGS-based panel comprising 84 genes in total was performed following the commercialized standard procedures established by CeGaT GmbH. The pathogenicity of each variant was evaluated according to the international ACMG criteria (Richards et al., 2015 ). Case report: At the age of 44 years, the now 48-year-old male patient with a negative family history noticed the first signs of gait unsteadiness. In the course, he developed profound symmetric calf atrophies, high arched feet, claw toes, and steppage gait. Except for the absent ankle jerk reflex, the deep tendon reflexes where surprisingly brisk. Sensory loss turned out comparably mild. Nerve conduction studies showed an axonal motor neuropathy in the legs, but were normal in the arms. The molecular genetic analysis revealed the heterozygous variant c.785T>C; p.Leu262Pro in the KIF5A gene, which has been described in association to SPG10 and/or an axonal CMT subtype following an autosomal dominant inheritance. The variant c.785T>C; p.Leu262Pro affects a highly conserved amino acid position within a functionally relevant domain. A change of secondary protein structure is conceivable as the linear leucine is replaced by proline, a cyclic amino acid. Several other missense mutations are described in the very close vicinity. The variant is predicted to be pathogenic by all available prediction programs. Its allele frequency in the healthy reference population is unknown. Unfortunately, co-segregation analyses could be performed since further family members were not available. For further evaluation, functional tests would be required. Discussion: On the current state of knowledge, the novel variant c.785T>C; p.Leu262Pro in KIF5A is evaluated as being a variant of uncertain significance. Due to the well matching phenotype (Liu et al., 2014 ), however, we consider it to be putatively pathogenic. This example underlines the necessity of precise phenotyping in the context of NGS-based multigene panels.